DISCOVERING IKLAINA, IS IT A DISTRICT CAPITAL OF THE PALACE OF NESTOR? - Streeton, Amy Lee (My University, 2011)
This paper aims to discover if the site of Iklaina near Pylos, Greece is a district capital to the Palace of Nestor. This paper looks at the background from which the Palace of Nestor came to be and the Linear B clay tablets that were found at the site. The texts in Linear B tablets discuss two provinces and the districts that fell under these provinces; nine in the Hither province and seven in the Further province. Also, the comparison between other district capitals mentioned in the tablets and that of a-pu? another district capital mentioned, which is believed to be the site of Iklaina. Is Iklaina a district capital? Is it one of the nine Hither province district capitals? A look at reports from digs in Iklaina will hopefully tell if the site fits the profile of a district capital.
Keywords: Greece -- Antiquities.; Archaeology and history.; Excavations (Archaeology) -- History.; Pylos (Greece) -- Palace of Nestor.